Assessment of the Effects of Acute and Repeated Exposure to Blast Overpressure in Rodents: Toward a Greater Understanding of Blast and the Potential Ramifications for Injury in Humans Exposed to Blast - Ahlers, Stephen T.; Vasserman-Stokes, Elaina; Shaughness, Michael C.; Hall, Aaron A.; Shear, Deborah A.; Chavko, Mikulas; McCarron, Richard M.; Stone, James R. (Frontiers in Neurology, 2012)
Mild traumatic brain injury (mTBI) resulting from exposure to improvised explosive devices (IEDs) has fueled a requirement to develop animals models that mirror this condition using exposure to blast overpressure (BOP). En route to developing a model of repeated exposure to BOP we sought to initially characterize the effects of acute BOP exposure in rodents, focusing specifically on the levels of BOP exposure that produced clinical mTBI symptoms. We first measured BOP effects on gross motor function on a balance beam. Separate groups of unanesthetized rats were exposed (in different orientations) to 40 kPa, 75 kPa and 120 kPa BOP exposure inside a pneumatically driven shock tube. Results demonstrated that rats exposed to 120 kPa demonstrated transient alterations or loss of consciousness indicated by a transient loss of righting and by increased latencies on the balance beam. The 120 kPa exposure was the threshold for overt pathology for acute BOP exposure with approximately 30% of rats presenting with evidence of subdural hemorrhage and cortical contusions. All animals exposed to 120 kPa BOP manifested evidence of significant pulmonary hemorrhage. Anterograde memory deficits were observed in rats exposed to 75 kPa facing the BOP wave and rats exposed to 120 kPa in the lateral (side) orientation. We next assessed repeated exposure to either lateral or frontal 40 kPa BOP in anesthetized rats, once per day for 12 days. Results showed that repeated exposure in the frontal, but not side, orientation to the BOP wave produced a transitory learning deficit on a Morris water maze (MWM) task as shown by significantly longer latencies to reach the submerged platform in the second and third blocks of a four block session. Implications of these data are discussed in relation to the manifestation of mTBI in military personnel exposed to IEDs. Finally, we suggest that there are multiple types of brain injury from blast.